PERAN BRAND IMAGE SEBAGAI MODERATOR CELEBRITY ENDORSER PADA KEPUTUSAN PEMBELIAN - Erawati, Sherly Hesti; Amalia, Novika Salsabila; Mauludin, Hanif; Liana, Yuyuk (STIE Malangkucecwara, 2023)
In the hypercompetitive era, the use of celebrity endorser s and brand image as determinants of purchasing decisions is still a major concern of marketing practitioners. The study aims to assess the influence of celebrity endorser s and brand image on purchasing decisions. The study involved 60 respondents who used a skincare product defined as Gen Z. Using the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) analysis, the study introduced a new perspective by positioning brand image as a moderation variable, a model with a limited precedent on previous research. The findings of this study reveal that celebrity endorser s as well as brand image have a significant influence on purchasing decisions. Furthermore, this study shows that brand image acts as a positive moderation. Strengthen the link between celebrity support and purchase decisions. The results highlight the multifaceted dynamics that play a role in consumer decision-making in the context of skin care beauty products, highlighting the important role of brand image as an important factor in increasing the influence of celebrity support on consumer purchasing decisions.